Conceitos-chave em Sociologia da Infância. Perspetivas Globais / Key concepts on Sociology of Childhood. Global Perspectives - Tomás, Catarina; Trevisan, Gabriela; Carvalho, Maria João Leote de; Fernandes, Natália (UMinho Editora, 2021)
This book intends to fill a gap that remains open in the scientific area of Sociology of Childhood. It brings together the contributions of 55 authors, recognized both nationally and internationally, from diverse countries, in a renewed critical analysis of contemporary issues, themes and challenges currently placed in research on childhood and on the child. The main goal is to share in a single volume a significant set of scientific reflections on key concepts of contemporary research in the area, in Portuguese and English, aiming to reach wider audiences around the globe.